Hsa_circ_0046523 Mediates an Immunosuppressive Tumor Microenvironment by Regulating MiR-148a-3p/PD-L1 Axis in Pancreatic Cancer - Fu, Xiaowei; Sun, Gen; Tu, Shuju; Fang, Kang; Xiong, Yuanpeng; Tu, Yi; Zha, Ming; Xiao, Tao; Xiao, Weidong (Frontiers in Oncology, 2022)
Background Circular RNAs (circRNAs) are a novel type of non-coding RNA, play an important role in the progression of tumors. However, the function and mechanism of circRNAs in regulating immune microenvironment of pancreatic cancer (PC) remain largely unclear. Methods The effects of hsa_circ_0046523 expression on proliferation, migration and invasion of PC cells were analyzed by CCK8 and Transwell assays. Flow cytometry was used to detect the proportion of CD4+ T cells, CD8+ T cells and Tregs in peripheral blood mononuclear cells (PBMCs) after co-culture, and the apoptosis, depletion and function of CD8+ T cells. The expression levels of immunoregulatory cytokines were detected by enzyme linked immunosorbent assay (ELISA). The dual-luciferase reporter was performed to determine the interaction between hsa_circ_0046523, miR-148a-3p, and PD-L1. Rescue experiments and PD-L1 blocking experiments were employed to investigate whether hsa_circ_0046523 exerts its biological function by miR-148a-3p/PD-L1 in PC. Furthermore, an immunocompetent murine PC model was established to confirm these findings. Results Hsa_circ_0046523 expression was remarkably upregulated in PC tissues and cell lines. Moreover, high expression of hsa_circ_0046523 was correlated with advanced pathological stage and poorer prognosis. Hsa_circ_0046523 overexpression promoted the proliferation, migration and invasion of PC cells in vitro. Co-culture experiments confirmed that forced expression of hsa_circ_0046523 could decrease the proportion of CD4+ and CD8+ T cells, as well as increase the proportion of Tregs among peripheral blood mononuclear cells (PBMCs). Meanwhile, hsa_circ_0046523 overexpression promoted the apoptosis and exhaustion of CD8+ T cells, inhibited CD8+ T cell function, increased the secretion of immunosuppressive cytokines IL-10 and TGF-β, and decreased the secretion of immune effector cytokines IFN-γ and IL-2 among PBMCs. Mechanistically, hsa_circ_0046523 exerted its biological function by binding to miR-148a-3p to upregulate PD-L1 expression in PC. Moreover, these immune modulating functions of miR-148a-3p/PD-L1 axis were also confirmed in an immunocompetent murine PC model. Conclusions Our study suggests that hsa_circ_0046523/miR-148a-3p/PD-L1 regulatory axis mediates PC immunosuppressive microenvironment and these molecules are expected to be new targets for remodeling tumor immune microenvironment of PC.